INOVASI NILAI EKONOMI MANFAAT IKAN RUCAH FERMENTASI KECAP IKAN KELOMPOK ISTRI NELAYAN RW 14, CILINCING JAKARTA UTARA - Khoirunnisa, Khoirunnisa; Hidajat, Koerniawan; Rahmadan , Yanuar (Nindikayla Institute, 2023)
Fish processing technology through fermentation of fish sauce as part of the diversification of fishery products is very promising to increase the income of fishing communities. North Jakarta in the Cilincing area, Kalibaru District is the largest fisheries producing area in DKI Jakarta. The purpose of community empowerment 1) for entrepreneurial empowerment solutions in the fishermen's environment looking for economic empowerment solutions, 2) additional economic income for fishing communities to improve the welfare of fishing communities, especially RW 14 Kalibaru. PKM method: 1) Socialization and 2) Training in making fermented fish sauce with pindang fish as raw material. The results of socialization for knowledge of fish processing innovations and fermented fish sauce in the fishermen's wives group of RW.14 Kalibaru residents. The results of training in making fermented fish sauce ± 10 days to 1 month with SS 201 tube tools loading ± 10 to 15 Kg of raw fish in a tight lid, room temperature is able to empower the diversification of fish processing product businesses to increase family economic income and the household industry of fishermen's wife groups